Design and fabrication of a cleaning cum cooling system for downdraft gasifier / Mohd Mahadzir Mohammud ... [et al.] - Mohammud, Mohd Mahadzir; Mansor, Muhammad Asyraf; Hemdi, Abdul Rahman; Yahaya, Mohamad Irwan (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
Biomass is the most abundant resources and available in all parts of Malaysia. It has the potential to be one of the best options for providing theon demand renewable fuel that can be utilized in various energy conversion technologies. The producer gas produced from biomass can be used to power electricity, thermal energy, or transportation fuels. However, the producer gas needs to be cleaned before being used. In the present paper the design and fabrication of cleaning cum cooling system is shown. The cleaning cum cooling system is used to filter the unwanted particle such as dust (particulate matter), tar and to absorb moisture produced by biomass gasification. The objectives are to design the cleaning cum cooling system by using SolidWorks 2016 software, to fabricate the mechanism by lab-scaled dimensions and to cool and clean the producer gas. The cleaning cum cooling system consists of three stages of filter (water scrubber, tar absorber and silica gel). Each filter has the same dimension size that is 110mm diameter and 400 mm height. The material used is Polyvinyl chloride (PVC) pipe. The results showed that temperature output of 30.9o C is obtained at point after the cleaning cum cooling system. Other than that, 8.5 grams of particulate matter and 32 grams of concentrated tar were trapped in the water scrubber and tar absorber filters. For the moisture test, 40 grams of water was found in the silica gels. These show that the producer gas has been cleaned where a blue flame was lastly obtained. It showed the producer gas is in a good condition.